2019
DOI: 10.1016/j.ecss.2019.106275
|View full text |Cite
|
Sign up to set email alerts
|

Salinity and growth effects on dimethylsulfoniopropionate (DMSP) and dimethylsulfoxide (DMSO) cell quotas of Skeletonema costatum, Phaeocystis globosa and Heterocapsa triquetra

Abstract: Salinity and growth effects on dimethylsulfoniopropionate (DMSP) and dimethylsulfoxide (DMSO) cell quotas of Skeletonema costatum, Phaeocystis globosa and Heterocapsa triquetra

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 80 publications
6
9
1
Order By: Relevance
“…In reaction to the stress generated by the salinity, P.antarctica could have increased its DSC cell contents. These results are similar to those observed for P.globosa by Speeckaert et al (2019) and could suggest oxidative stress in the cell. Indeed, as suggested by Liu et al (2012) in the halophile green algae Dunaliella salina, hypo-osmotic stress at S20 could induce the accumulation in the chloroplast of reactive oxygen species (ROS) such as H2O2 or the hydroxyl radical • OH.…”
Section: Discussionsupporting
confidence: 90%
“…In reaction to the stress generated by the salinity, P.antarctica could have increased its DSC cell contents. These results are similar to those observed for P.globosa by Speeckaert et al (2019) and could suggest oxidative stress in the cell. Indeed, as suggested by Liu et al (2012) in the halophile green algae Dunaliella salina, hypo-osmotic stress at S20 could induce the accumulation in the chloroplast of reactive oxygen species (ROS) such as H2O2 or the hydroxyl radical • OH.…”
Section: Discussionsupporting
confidence: 90%
“…I0; 100 μmol photons m −2 s −1 and 15 • C) were found to differ between species investigated, with the diatom possessing much less DMSP:Chl-a than the dinoflagellate and the Prymnesiophyceae. DMSP:Chl-a ratios measured in our cultures also agreed with previous studies conducted on H. triquetra (122.7 ± 27.7 mmolS:g Chl-a in average) and P. globosa (82.3 ± 11.5 mmolS:g Chl-a), maintained in similar environmental conditions (Keller et al, 1989;Niki et al, 2000;Speeckaert et al, 2018Speeckaert et al, , 2019Stefels et al 2007). For S. costatum, values were similar to those of Speeckaert et al (2018), who applied the same methodology on the same strain, but differed from other studies reporting lower DMSP:Chla ratio (4.5 to 11.8 mmolS:g Chl-a, in average; Keller and Korjeff-Bellows 1996;Sunda et al, 2007;Stefels et al, 2007;Spielmeyer et al, 2011;Speeckaert et al, 2019).…”
Section: Dmsp P and Dmso P Contents Vary Among Phytoplankton Species Investigatedsupporting
confidence: 92%
“…DMSP:Chl-a ratios measured in our cultures also agreed with previous studies conducted on H. triquetra (122.7 ± 27.7 mmolS:g Chl-a in average) and P. globosa (82.3 ± 11.5 mmolS:g Chl-a), maintained in similar environmental conditions (Keller et al, 1989;Niki et al, 2000;Speeckaert et al, 2018Speeckaert et al, , 2019Stefels et al 2007). For S. costatum, values were similar to those of Speeckaert et al (2018), who applied the same methodology on the same strain, but differed from other studies reporting lower DMSP:Chla ratio (4.5 to 11.8 mmolS:g Chl-a, in average; Keller and Korjeff-Bellows 1996;Sunda et al, 2007;Stefels et al, 2007;Spielmeyer et al, 2011;Speeckaert et al, 2019). The DMSO p -to-chlorophyll-a (DMSO p :Chl-a) ratios measured in this study were a bit higher than values reported in the literature, with 0.2 ± 0.2 for the diatoms, 1.5 ± 0.4 for the Prymnesiophyceae and 3.9 ± 4.3 mmolS:g Chl-a for the dinoflagellates (Simó et al, 1998;Hatton and Wilson, 2007;Bucciarelli et al, 2013;Speeckaert et al, 2019).…”
Section: Dmsp P and Dmso P Contents Vary Among Phytoplankton Species Investigatedsupporting
confidence: 92%
“…Moreover, its low molecular weight allows rapid entry through the cell membrane, in addition to modulating the stability of the phospholipid bilayer. Electrostatic interactions of DMSO with phospholipids have been suggested, appearing to be critical for membrane cryoprotection [ 81 , 82 ].…”
Section: Plant Vitrification Solutionmentioning
confidence: 99%